Portrait of indonesian usage in gafabaca's children's story book series; gafabaca series 1 and 2, fish series, and cat series - Niknik M Kuntarto* (Universitas Indraprasta PGRI, 2017)
Talking is one and the four skills in language that is productive and active Because of them that, a lot of foreign speakers have difficulty when first learning to speak in Indonesian one problem often encountered is the limited vocabulary that is owned by a foreign speaker Many instructional media offered to increase the amount of vocabulary for speakers Asung, one of which is the media images media images can increase 400% ability of foreign speakers in remembering vocabulary in the classroom, therefore, the authors developed a media joyful learning in the form of a comic comics is a combination of pictures and words capable of arouse and excite the foreign speakers to continue to learn to speak in a way that is fun this paper will describe a form of learning berbucara who could inspire and stimulate foreign speakers as well as fun in the classroom through the comic making it easier for foreign speakers achieve the goal of learning to speak.